HERVd: the Human Endogenous RetroViruses Database: update - Paces, Jan; Pavlícek, Adam; Zika, Radek; Kapitonov, Vladimir V; Jurka, Jerzy; Paces, Václav (Nucleic acids research, 2004)
An elaboration of HERVd (http://herv.img.cas.cz) is being carried out in two directions. One of them is the integration and better classification of families that diverge considerably from typical retroviral genomes. This leads to a more precise identification of members with individual families. The second improvement is better accessibility of the database and connection with human genome annotation.
Keywords: ukládání a vyhledávání informací; Endogenous Retroviruses; databáze genetické; internet; endogenní retroviry; Databases, Genetic; lidé; genom lidský; Humans; Computational Biology; Information Storage and Retrieval; Genome, Human; výpočetní biologie; Internet